Variability of a closed, rebreathing setup for multiple breath wash-out testing in children - Pittman, Jessica E.; Johnson, Robin C.; Jones, Paul W.; Davis, Stephanie D. (Pediatric pulmonology, 2012)
Objective The multiple breath wash‐out technique (MBW) that measures lung clearance index (LCI) and functional residual capacity (FRC) may be more sensitive than spirometry for identification of early obstructive airways disease. The open MBW setup using mass spectrometry referenced in previous publications is not readily available in the U.S. Our objective was to assess validity and sensitivity of a commercially available device that uses a closed (rebreathing) setup with photoacoustic spectroscopy for MBW testing. Study Design and Methods Subjects aged 5–21 who were either healthy or had a history of cystic fibrosis were enrolled. Subjects completed MBW (Innocor device; Innovision, Denmark) and spirometry; measures obtained included LCI, FRC, and forced expiratory volume in 1 sec, as well as changes in end‐tidal carbon dioxide levels (CO2) and tidal volume during MBW testing. Results Seventeen subjects attempted a total of 76 MBW maneuvers; 80% were completed and 60% met criteria for acceptability; most were unacceptable due to errors in the tracer gas curve. Substantial intra‐subject variability for LCI and FRC were noted (mean 26% ± 55 and 36% ± 63, respectively). Subjects were also noted to have significant increases in exhaled CO2 and tidal volume during MBW testing. Conclusions In our initial experience using a commercially available closed setup for MBW testing, we found a significant degree of intra‐subject variability leading us to suspend testing. Variability could be due to hypercapnea and instability of tidal breathing secondary to the rebreathing setup. Further studies are needed to better understand the closed system MBW setup. Pediatr Pulmonol. 2012; 47:1242–1250. © 2012 Wiley Periodicals, Inc.